Weevils in the salad - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The water weed commonly referred to as water lettuce, Pistia stratiotes, is causing grave concern, particularly in the Senegal River valley. For several Years, some parts of Lake Guiers to the north of Dakar have been covered with a thick carpet of...